Flashpoint in Ukraine how the US drive for hegemony risks World War III - Lendman, Stephen (Clarity Press, Inc., 2014)
"Twenty-two geopolitical analysts provide an alternative vision to the fraudulent Western narrative on events in Ukraine and alert the world to the danger of a much wider war."--Page 4 of cover.